Mini Tinjauan Literatur Pemanfaatan Software Triangulos untuk Berpikir Komputasi Siswa - Shilva Syahbina; Yahfizham Yahfizham (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Computational thinking skills are now one of the main skills in 21st century education. Not only does it support mastery of technology, this ability is also very important in understanding and solving problems systematically. This study aims to review in depth the potential for utilizing Triangulos software as an innovative learning medium to improve students' computational thinking skills, especially in mathematical geometry material. The study used a literature review approach by tracing primary and secondary sources from 2020–2024. The results of the analysis show that the use of Triangulos can encourage students to develop algorithmic thinking patterns, spatial visualization, and problem-solving skills. In addition, this application also supports independent and collaborative learning, and has the potential to increase student motivation and activeness in class. These findings recommend the integration of Triangulos in mathematics learning as one of the efforts to innovate education in the digital era. Further empirical research is highly recommended to test the effectiveness of this application at various levels of education.